MAKING COOLBOX USING A JUNE SACK WITH RICE HUSK (Oryza sativa) INSULATION AND CORN COB (Zea mays) - Thahir, Muhammad Agam; Anzuardhi, Anzuardhi; Amrullah, T.; Ukhty, Nabila; Nasution, Muhammad Arif (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Fish quality is very important to determine the selling price of fish in the market; therefore, it is necessary to have special handling in storage so that the quality of fish does not decrease. Fishermen usually use styrofoam-insulated coolboxes to maintain fish quality. This study aims to determine the lowest temperature and temperature stability. This research was conducted in April-June 2022 at the Integrated Fisheries Laboratory, Faculty of Fisheries and Marine Science, Teuku Umar University. The method used is a quantitative experimental method using a completely randomized design (CRD) with 1 control, 2 treatments, and 3 replicates. Tests were carried out by measuring the temperature of the coolbox room filled with 3 kg of bulk ice and looking at temperature changes within 9 hours. The lowest temperature test results contained in the rice husk coolbox were 17.4°C, the corn cob coolbox had the lowest temperature of 19.3°C, and in the styrofoam coolbox (control), the lowest temperature obtained was 13.6°C. The temperature comparison between the styrofoam coolbox, rice husk insulation coolbox, and corn cob insulation coolbox shows that, in terms of the lowest temperature point, the styrofoam coolbox is still better than the rice husk and corn cob coolbox, while the rice husk coolbox is still lower in temperature than the corn cob coolbox.